2010
DOI: 10.1365/s10337-010-1763-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Gentamicin Sulphate Composition and Related Substances in Pharmaceutical Preparations by LC with Charged Aerosol Detection

Abstract: A new, simple and repeatable liquid chromatography method with charged aerosol detection (LC-CAD) for the determination of gentamicin sulphate composition and related substances has been developed. Gentamicin lacks of chromophores, therefore its determination is quite problematic. Using a universal CAD enables to achieve good separation without sample derivatization. Mass spectrometry was employed to confirm the LC-CAD peak profile. The proposed method was validated and applied for the determination of gentami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 36 publications
0
31
0
1
Order By: Relevance
“…Gentamicin is not a pure compound. The US Pharmacopeial Convention (USP) specifies 25-50% gentamicin C1; 10-35% gentamicin C1a; and 25-55% gentamicin C2 + C2a, whereas the European Pharmacopoeia requires 20-40% gentamicin C1; 10-30% gentamicin C1a; 40-60% gentamicin C2 + C2a + C2b; and no more than 3% sisomycin (6). Sisomycin is one of several minor components, including gentamicin A, B, B1, garamine, and ring C.…”
Section: Gentamicin B1 Is the Major Ptc Readthrough Component In Pharmentioning
confidence: 99%
See 2 more Smart Citations
“…Gentamicin is not a pure compound. The US Pharmacopeial Convention (USP) specifies 25-50% gentamicin C1; 10-35% gentamicin C1a; and 25-55% gentamicin C2 + C2a, whereas the European Pharmacopoeia requires 20-40% gentamicin C1; 10-30% gentamicin C1a; 40-60% gentamicin C2 + C2a + C2b; and no more than 3% sisomycin (6). Sisomycin is one of several minor components, including gentamicin A, B, B1, garamine, and ring C.…”
Section: Gentamicin B1 Is the Major Ptc Readthrough Component In Pharmentioning
confidence: 99%
“…gentamicin (6). Testing >98% pure samples of the minor aminoglycosides found in the gentamicin batches showed that gentamicin B1 (Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…However, derivatization methods have several inherent problems that limit further applications including the complexity of derivatization reactions and possible formation of by-products or degradation products during the derivatization procedure. More recently, the charged aerosol detection (CAD) reported by Dixon and Peterson [13] has been applied for the detection of compounds lacking UV-absorbing chromophores [14][15][16][17][18][19]. The CAD is a relatively new universal detection technology with high sensitivity and a broad dynamic range.…”
Section: Introductionmentioning
confidence: 99%
“…A gentamicina é constituída por uma mistura de substâncias designadas como gentamicina C1, C1a, C2, C2a e, ainda, por um componente em menor quantidade, o C2b (Figura 2) (COOPER; MARIGLIANO;TRAUBEL, 1971;COOPER;YUDIS, 1971;COPPER et al, 1971;BAERE;BACKER, 2000;KÜHN et al, 2008;CSERVEN;RADULOVI;VU, 2011;CAUDRON et al, 2013;BIJLEVELD et al, 2014). TURNIPSEED et al, 2009;STYPULKOWSKA et al, 2010;BAIETTO et al, 2010;VUCICEVIC-PRCETIC;CSERVENAK;RADULOVIC, 2011;LEHOTAY et al, 2013;BIJLEVELD et al, 2014). Em alguns casos, a derivatização do analito foi necessária (TURNIPSEED et al, 2009).…”
Section: Objetivos Específicosunclassified